GERAKAN CUCI TANGAN CERIA (GENTARIA): IMPLEMENTASI EDUKASI BERBASIS PKM UNTUK MEMBANGUN BUDAYA PHBS - asri dewi (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Clean and Healthy Living Behavior (CHLB) need to be instilled starting in elementary school age as a preventive effort to reduce the risk of infectious diseases. One important indicator of CHLB constitutes the routine of Washing Hands with Soap (WHWS). Based on initial observations at SDN Godog 1 Karangpawitan, It was found that most students have not yet adopted proper handwashing techniques. This Community Service activity, conducted by the Pharmacy Study Program of Universitas Garut, intended to enhance students' knowledge and skills regarding WHWS according to WHO standards. The methods used included counseling, demonstration of the six steps of handwashing, joint practice, and questionnaires. The questionnaire results reveal an increase in students' knowledge and skills in implementing the six steps of WHWS. Educational reinforcement was provided through the distribution of WHWS step-by-step posters. This activity contributes to forming sustainable health behaviors in elementary school students.